Water Quality Coupling Model Classifications and Their Applications - WANG Wei; WANG Xiaoqing (Renmin Zhujiang)
Water quality model is widely used in water quality simulation, prediction and auxiliarydecision-making, which is an important tool to study water pollution and control waterenvironment. In recent years, attention has been paid to the study of water quality couplingmodel, which can overcome the limitations of using a single model and improve the simulationaccuracy. This paper systematically introduces three types of water quality coupling models whichare widely used at home and abroad, mainly including the coupling model composed of multiple waterquality models, hydrological-water quality coupling model, GIS-water quality coupling model,focuses on the internal development driving force and application of each coupling model,discusses the advantages of the coupling model in practical application,summarizes the advantagesand disadvantages of different modes of water quality coupling models, and proposes the futuredevelopment prospect of water quality coupling model according to the difficulties existing in themodel coupling modes.